Qualitative Research Methods in Public Relations and Marketing Communications - Daymon, Christine, Immy Holloway (Routledge, 2005)
Qualitative Research Methods in Public Relations and Marketing Communications will be invaluable for those undertaking research methods courses on public relations and marketing communication degrees, as well as those working on a dissertation.